(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The work examines the impact of radiation on human life. In nuclear medicine, doctors inject patients with a radioactive substance that accumulates in the part of the human body that is the target. When the radiation leaves the body, it is recorded, allowing doctors to draw conclusions about the physiological functions of an organ or tissue. It also shows the ways in which the artificial radioisotope 131 I is produced in a nuclear reactor.